2018
DOI: 10.3390/proteomes6040053
|View full text |Cite|
|
Sign up to set email alerts
|

Proteomic Analysis of the Spinophilin Interactome in Rodent Striatum Following Psychostimulant Sensitization

Abstract: Glutamatergic projections from the cortex and dopaminergic projections from the substantia nigra or ventral tegmental area synapse on dendritic spines of specific GABAergic medium spiny neurons (MSNs) in the striatum. Direct pathway MSNs (dMSNs) are positively coupled to protein kinase A (PKA) signaling and activation of these neurons enhance specific motor programs whereas indirect pathway MSNs (iMSNs) are negatively coupled to PKA and inhibit competing motor programs. An imbalance in the activity of these tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 94 publications
(136 reference statements)
0
15
0
Order By: Relevance
“…To identify signaling nodes that are regulated by fucosylation, we treated 4T1 metastatic mammary tumor cells with the fucosylation inhibitor, 2FF, or DMSO ( Supplementary Figure S1A ) and performed TMT proteomics ( Supplementary Figure S1B ) [ 27 ]. This analysis identified 5750 proteins and quantified 5288 of them by MS2-based TMT.…”
Section: Resultsmentioning
confidence: 99%
“…To identify signaling nodes that are regulated by fucosylation, we treated 4T1 metastatic mammary tumor cells with the fucosylation inhibitor, 2FF, or DMSO ( Supplementary Figure S1A ) and performed TMT proteomics ( Supplementary Figure S1B ) [ 27 ]. This analysis identified 5750 proteins and quantified 5288 of them by MS2-based TMT.…”
Section: Resultsmentioning
confidence: 99%
“…Mechanistically, how spinophilin decreases surface expression could involve clathrin-mediated endocytosis given that we have previously observed clathrin in spinophilin co-IPs (Watkins et al, 2019) and GluN2B-containing NMDA receptors undergo clathrin-mediated endocytosis (Wu et al, 2017b). Moreover, alterations in vesicle trafficking could involve the motor protein, myosin-Va, since we have previously found that both spinophilin and GluN2B interact with Myosin-Va (Baucum et al, 2013;Hiday et al, 2017;Salek et al, 2019; and others have shown that myosin-Va associates with vesicles and is critical in AMPA receptor trafficking and function (Correia et al, 2008;Rudolf et al, 2011).…”
Section: Discussionmentioning
confidence: 96%
“…The author wishes to make the following corrections to the methods section of their paper [1]: The corrections include: (1) Replace the sentence "Mouse striatum (including both dorsal and ventral (accumbens) striatum or olfactory tubercle) was homogenized and sonicated in 1 mL in a low-ionic strength Tris buffer containing 20 mM Tris, 10 mM DTT, 2 mM 0.5 M EDTA, 10% Triton X-100, 1% protease inhibitor cocktail (Bimake, Houston, TX, USA)" with "Mouse striatum (including both dorsal and ventral (accumbens) striatum or olfactory tubercle) was homogenized and sonicated in 1 mL in a low-ionic strength Tris buffer containing 2 mM Tris-HCl, 1 mM DTT, 2 mM EDTA, 1% Triton X-100, and 1X protease inhibitor cocktail (Bimake, Houston, TX, USA)"; (2) replace the sentence "magnetic separation in an immunoprecipitation wash buffer (50 mM NaCl, 50 mM Tris-HCl pH 7.5, 0.5% (v/v) Triton X-100)" with "magnetic separation in an immunoprecipitation wash buffer (150 mM NaCl, 50 mM Tris-HCl pH 7.5, 0.5% (v/v) Triton X-100)".…”
mentioning
confidence: 99%